IADC/SPE International Drilling Conference and Exhibition 2020
DOI: 10.2118/199634-ms
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Dynamics Model to Mitigate High Frequency Torsional Oscillation

Abstract: In recent years, the phenomenon of drill string torsional oscillation at frequencies over 50 Hz has been well documented. This high frequency torsional oscillation (HFTO) creates cyclic fatigue loading on bits and drilling tools within the bottom hole assembly (BHA) and thus limits tool life and drilling performance. However, few models exist which can predict occurrence of HFTO and its severity. To our knowledge; none of these models consider the entire drilling system including the bit-rock interaction, down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Typically, the collar cracking with the crack propagating on a plane 45°from the collar axis is induced by excessive HFTO [62].…”
Section: High-frequency Torsional Oscillation (Hfto)mentioning
confidence: 99%
See 3 more Smart Citations
“…Typically, the collar cracking with the crack propagating on a plane 45°from the collar axis is induced by excessive HFTO [62].…”
Section: High-frequency Torsional Oscillation (Hfto)mentioning
confidence: 99%
“…Shen et al [62] summarized two mechanisms that cause HFTO to be contained in parts of the BHA or lower drillstring.…”
Section: 21mentioning
confidence: 99%
See 2 more Smart Citations
“…Torsional vibration is inevitable during the drilling process. Close DA et al found that when the frequency of torsional vibration reaches above 50 Hz, torsional vibration can cause fatigue damage to the drilling tool [17]. When the severity of torsional vibration increases until the rotation of the drill string can be stagnated, the torsional vibration is transformed into a more harmful stick-slip vibration [5,18].…”
Section: Introductionmentioning
confidence: 99%